Application of Balloon AngioplaSty with the dIstal protection of Stent Retriever (BASIS) technique for acute intracranial artery atherosclerosis-related occlusion - Yi, Ting-yu; Wu, Yan-min; Lin, Ding-lai; Pan, Zhi-nan; Zheng, Xiu-fen; Gan, Ji; Wu, Mei-hua; Lin, Xiao-hui; Chen, Rong-cheng; Zeng, Li-san; Chen, Wen-huo (Frontiers in Neurology, 2022)
Background Endovascular therapy (EVT) is complex in the context of intracranial atherosclerosis (ICAS)-related large vessel occlusion (LVO) and the re-occlusion rates are high due to residual stenosis, the procedure time is long and the optimal EVT technique is unclear. The Balloon AngioplaSty with the dIstal protection of Stent Retriever (BASIS) technique is a novel thrombectomy technique that allows emergent balloon angioplasty to be performed via the wire of the retrieval stent. Our study presents our initial experience with the BASIS technique in ICAS-related LVO and assesses its feasibility. Method In patients with ICAS-related LVO treated with BASIS, clinical and angiographic data were retrospectively analyzed. Angiographic data included first-pass reperfusion (PFR), the rate of residual stenosis, distal emboli, and re-occlusion post-procedure. The Extended Thrombolysis in Cerebral Infarction (eTICI) scale was used to assess reperfusion extent, and an eTICI score ≥2b was defined as successful perfusion. Clinical outcome was evaluated at 3 months (modified Rankin score [mRS]), and an mRS ≤ 2 was defined as a good clinical outcome. Results A total of seven patients with ICAS-related LVO were included, and the median age of the patients was 76 years. All patients achieved eTICI 3 reperfusion and FPR. The residual stenosis rate ranged from 5 to 10%. None of the patients had re-occlusion post-procedure. The median puncture-to-reperfusion time was 51 min. None of the patients had a symptomatic cerebral hemorrhage, re-occlusion, distal embolism, and dissection. Good clinical outcomes were observed in four patients (4/7, 57.1%), and 1 patient (1/7, 14.3%) died. Conclusion The BASIS technique is feasible and safe for treating acute ICAS-related LVO.